The Influence Of Marketing Strategy (Marketing Mix) On Purchase Decisions At PT. Kreativ Niaga Mandiri Bengkulu - Romanza, Nano; Hanila , Siti; Adjie , Dwi Nova (Utami Publisher, 2025)
The purpose of this study is to find out whether the marketing strategy (marketing mix) of products, price, place, and promotions have a significant effect simultaneously on the purchase decision at PT. Kreativ Niaga Mandiri Bengkulu. This type of research is quantitative with a causal associative design. The data collection method in this study uses a questionnaire technique, with a sample of 75 respondents. The results of this study showed that the multiple linear regression Y = 3.917 + 0.212 X1 + 0.261 X2 + 0.260 X3 + 0.190 X4 + 0.874. Where the coefficient has a positive and significant value, it means that there is a positive or unidirectional relationship between the variables of Product (X1), Price (X2), Place (X3), and Promotion (X4) in determining the return of purchase decisions. The results of the product variable test showed a calculation of 2,732 > a table of 1,993 and a definition of 0.008 < 0.05, then the results of hypothesis Ha were accepted and Ho was rejected, meaning that the product had a positive and significant effect on the purchase decision. The results of the price variable test showed a calculation of 4,690 > a table of 1,993 and a definition of 0.000 < 0.05, then the result of hypothesis Ha was accepted and Ho was rejected, meaning that price had a positive and significant effect on the purchase decision. The results of the place variable test showed a calculation of 3,627 > a table of 1,993 and a definition of 0.001 < 0.05, then the results of hypothesis Ha were accepted and Ho was rejected, meaning that the place had a positive and significant effect on the purchase decision. The results of the promotion variable test showed that the calculation was 2,524 > 1,993 and the definition was 0.014 < 0.05, then the results of hypothesis Ha were accepted and Ho was rejected, meaning that the place had a positive and significant effect on the purchase decision. Based on the comparison of the value of Fcal with Ftable, the value of Fcal is greater than that of Ftable, which is 493,131 > 2.50, then it is concluded that accepting the hypothesis, meaning that there is a simultaneous influence between the product (X1), price (X2), place (X3), promotion (X4) significantly contributes to the purchase decision. This is seen at a significance level of 0.000 < 0.05.